Fault Movement and Uplift Mechanism of Mt. Gongga, Sichuan Province, Constrained by Co-Seismic Deformation Fields from GNSS Observations - Zheng Xu; Yong Li; Guixi Yi; Shaoze Zhao; Shujun Liu (Remote Sensing)
On 5 September 2022, a Mw 6.6 earthquake occurred in Luding, Sichuan Province, China. The epicenter of this earthquake was located in the vicinity of Mt. Gongga. The China Earthquake Administration employed the Global Navigation Satellite System (GNSS) to conduct concurrent deformation field monitoring of the main fault associated with the Luding earthquake. The research area surrounding Mt. Gongga exhibits intricate structural and dynamic processes. However, previous studies have lacked a comprehensive three-dimensional analysis of the uplift mechanism of Mt. Gongga. This study utilizes GNSS data to constrain simulations and employs the FLAC3D numerical model to simulate the primary fault movement during the earthquake and the subsequent changes in the uplift of Mt. Gongga. These investigations are supported by seismic analysis, mechanical analysis, and inversion studies, facilitating the formulation of its uplift mechanism. The results indicate the following: (1) The seismic source analysis of the earthquake reveals a steep dip angle of the primary fault plane, with a predominant inclination toward the northeast. (2) Numerical simulations demonstrate a consistent correlation between the horizontal displacement pattern and the arcuate structure of the Sichuan–Yunnan block, promoting the counterclockwise uplift of Mt. Gongga. The vertical displacement pattern indicates that this earthquake accelerated the overall uplift of Mt. Gongga. (3) Mt. Gongga undergoes a multiple coupling uplift mechanism characterized by “clockwise uplift + rotational flexure + asthenospheric upwelling”. Seismic analysis, mechanical analysis and the results of numerical inversion serve as a useful basis for understanding the uplift of Mt. Gongga and for understanding high mountain uplift in orogen-foreland systems in general.